Analisis Kegunaan, Kemudahan, Sikap Penggunaan Teknologi Terhadap Penggunaan Mobile Banking BSI pada Generasi Z dengan (TAM) - Ari Wibowo; Hanif Hanif; Muhammmad Iqbal Fasa (ARBITRASE: Journal of Economics and Accounting, 2026)
This study aims to analyze the influence of perceived usefulness, perceived ease of use, and attitude toward using technology on the use of BSI mobile banking among Generation Z in Bandar Lampung using the Technology Acceptance Model (TAM) approach. The development of digital technology encourages the Islamic banking sector to provide digital-based services that meet the needs of modern society which prioritizes convenience and speed in transactions. Generation Z as a digital native generation has a high level of technological adaptation, making them a potential group in the use of mobile banking services. This study uses a quantitative method with data collection techniques through questionnaires distributed to Generation Z users of BSI Mobile in Bandar Lampung. and there are 100 respondents to be tested. The independent variables in this study consist of perceived usefulness, perceived ease of use, and attitude toward using technology, while the dependent variable is the use of BSI mobile banking. Data analysis was conducted using a statistical approach to determine the partial and simultaneous effects among variables. The results of this study are expected to show that perceived usefulness, perceived ease of use, and attitude toward using technology have a positive influence on the use of BSI mobile banking among Generation Z in Bandar Lampung. This study is expected to provide a theoretical contribution to the development of Technology Acceptance Model (TAM) studies in the Islamic banking sector and become an evaluation material for Bank Syariah Indonesia in improving the quality of digital banking services according to the needs of Generation Z. This research contributes to the growing body of evidence that the TAM model remains relevant in Islamic banking, particularly among Generation Z. The results suggest that attitudes toward technology and ease of use are more influential than perceived benefits. Furthermore, this research provides insights for Bank Syariah Indonesia to develop digital services that better align with the habits and needs of younger users.